2007
DOI: 10.1002/nau.20506
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal pelvic response to cough in women with stress urinary incontinence

Abstract: Some women with SUI exhibit an altered pattern of the PFM response during increasing coughing efforts. The lack of this modulation of PFM response to stress may be one of the pathophysiologic factors of SUI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 25 publications
0
58
1
2
Order By: Relevance
“…To guarantee continence, the PFM must be able to contract strongly [9], rapidly, and reflexively [10,11]. The ability of PFM to generate rapid and strong contractions results in the generation of an adequate squeeze pressure in the proximal urethra, which maintains a pressure higher than that in the bladder, thus preventing leakage [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To guarantee continence, the PFM must be able to contract strongly [9], rapidly, and reflexively [10,11]. The ability of PFM to generate rapid and strong contractions results in the generation of an adequate squeeze pressure in the proximal urethra, which maintains a pressure higher than that in the bladder, thus preventing leakage [12].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid PFM contractions are crucial for maintaining continence preceding an abrupt rise in the intra-abdominal pressure associated with coughing and sneezing [11,12]. Several studies showed that the PFM function regarding rate of force development was impaired in incontinent women compared with continent women [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…L'implication du système neuromusculaire dans la continence est bien établie [30][31][32][33][34][35][36].…”
Section: Interprétations Et Résultats Des Explorations éLectrophysiolunclassified
“…Nos travaux semblent également montrer qu'il existe une anomalie du profil de réponse neuromusculaire pelvipérinéale à l'effort chez les femmes ayant une IUE par rapport aux femmes continentes [47]. On peut ainsi faire l'hypothèse qu'un défaut de modulation de la contraction musculaire pelvi-périnéale lors de l'effort puisse être un facteur causal d'IUE, de façon isolée ou associée à d'autres facteurs comme l'insuffisance sphinctérienne et l'hypermobilité cervico-urétrale.…”
Section: Modulation De La Réponse Réflexe Périnéaleunclassified